Application of radioisotope XRF and thermoluminescence (TL) dating in investigation of pottery from Tell AL-Kasra archaeological site, Syria. (November 2015) - Abboud, R.; Issa, H.; Abed-Allah, Y.D.; Bakraji, E.H.
Abstract: Statistical analysis based on chemical composition, using radioisotope X-ray fluorescence, have been applied on 39 ancient pottery fragments coming from the excavation at Tell Al-Kasra archaeological site, Syria. Three groups were defined by applying Cluster and Factor analysis statistical methods. Thermoluminescence (TL) dating was investigated on three sherds taken from the bathroom (hammam) on the site. Multiple aliquot additive dose (MAAD) was used to estimate the paleodose value, and the gamma spectrometry was used to estimate the dose rate. The average age was found to be 715±36 year. Highlights: Providing new additional data of Syrian archaeological ceramics. This work investigates both elemental content and dating of Syrian ceramics. Elemental analysis and dating were performed by XRF and TL dating respectively.